The Impact of Currency Depreciation on International Trade Flows - 김도연 (Review of International Money and Finance, 2012)
The currency devaluation can boost domestic employment and foreign demand of exports. As the price of domestic currency falls, so does the real price of exporting goods. Imports become more expensive too. We explain the impact of currency depreciation on international trade between two countries with a simple model. We suggest a general two-country two-goods model to explain how currency depreciation works in between two countries. We adopt a constant price model, in which currency depreciation helps domestic exporters increasing their revenue under the assumption of unchangeable price level. We also adopt a market clearing model, in which the producer in currency devaluated country, again, earns more revenue than the other country. The model, however, shows that currency devaluation cannot be a long-term strategy, but only a temporary stimulus package. KCI Citation Count: 0